The use of tritiated water to estimate the kinetics of body water in lactating Borana cows under ranch condition - Bussa, N. (1984)
Two of the major problems of cattle production in the semi-arid regions are the effect of water deprivation and low nutrient intake during the dry season. The presence of adequate water in body tissues is an essential pre-requisite for normal maintenance of life, and water is a fundamental constituent of all living cells. Therefore, its absence brings serious complications and reduces the expected productivity of livestock. In this study an attempt was made to investigate the effect of water restriction on body water pool water turnover and water consumption of 30 lactating Borana cows under ranch condition. Live weight (kg), Body water (liters) water turnover (liter/day, liter/100 kg/day, mI/kg/day, ml/liter/day and ml / liter (0.82) / day) and water consupmtion (liter/drink,liter/l00 kg/drink, liter/day and liter/l00 kg/day) were tested in completely Randomized Design.